Optimizing electric corona treatment for hydroxypropylated starch-based coatings. (1st October 2018) - Lyytikäinen, Johanna; Ovaska, Sami-Seppo; Soboleva, Ekaterina; Rinkunas, Ringaudas; Lozovski, Tadeus; Maldzius, Robertas; Sidaravicius, Jonas; Johansson, Leena-Sisko; Backfolk, Kaj
Highlights: Dispersion barrier coatings were treated with corona and plasma treatments. Plasma treatment enhanced the wettability more efficiently. Both physical and chemical changes occurred after plasma treatment. The use of biopolymer gave different response on plasma and corona treatment. Abstract: The aim of this investigation was to determine the role of negative direct current and alternating current (plasma) corona treatments in modification of bio-based dispersion barrier coatings and the response of replacing fossil-based binder with a thermoplastic bio-based binder (starch). The study emphasizes the importance of understanding and optimizing electric corona discharge in order to obtain high oxidation level without harming the substrate and causing unintentional treatment of the reverse side. The coatings were exposed to different corona treatment conditions using a novel developed sheet-fed laboratory-scale device. Corona-induced topographical, mechanical and surface chemical changes were observed from atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and contact angle and surface energy measurements. XPS results indicated further that partial starch decomposition occurred after plasma treatment. Coated surfaces became substantially smoother after both treatments suggesting that nanoparticle migration and re-orientation effects occurred. Additionally, reverse side effects and strike through were also discussed.